The role of fibroblast growth factor 18 in cancers: functions and signaling pathways - Zhou, Yiming; Sun, Sizheng; Ling, Tao; Chen, Yongzhen; Zhou, Rongzhong; You, Qiang (Frontiers in Oncology, 2023)
Fibroblast growth factor 18(FGF18) is a member of the fibroblast growth factor family (FGFs). FGF18 is a class of bioactive substances that can conduct biological signals, regulate cell growth, participate in tissue repair and other functions, and can promote the occurrence and development of different types of malignant tumors through various mechanisms. In this review, we focus on recent studies of FGF18 in the diagnosis, treatment, and prognosis of tumors in digestive, reproductive, urinary, respiratory, motor, and pediatric systems. These findings suggest that FGF18 may play an increasingly important role in the clinical evaluation of these malignancies. Overall, FGF18 can function as an important oncogene at different gene and protein levels, and can be used as a potential new therapeutic target and prognostic biomarker for these tumors.